The effect of dual versus mono medium teaching on the ability of bilingual, typically developing children to label graphic symbols in two languages - Tonsing, Kerstin Monika (University of Pretoria, 2018)
Mini Dissertation (M(AAC))--University of Pretoria, 2017.